Effects of Urban Expansion in the Choice of Commuting Modes by the Population of Metropolitan Areas - Braçe, Olta (Revista de Estudios Andaluces, 2018)
At present, urban expansion represents one of the major challenges that cities must resolve. The phenomenon of urban growth involves a spatial transformation that has been accompanied by negative effects such as extensive use of land, the excessive use of motorized means of transport, environmental impacts, increased costs or social segregation. Socio-spatial distances are accentuated and consequently increases the use of private vehicles and peoples spend more time in transportation. The rural landscape is placed by a monotonous landscape without great architectural values. The main objective of this study is to analyze the reasons and effects of urban expansion in the choice of the means of transport used by the population of the metropolitan area of Seville in their commuting. Through a descriptive analysis, it has been revealed as the population living in this space use motorized transport as the first and main option. Despite the existence of several bus lines and the construction of the subway as a public transport infrastructure of great capacity and quality, the percentage of population that uses public transport modes is quite limited